Reaping the Benefits of Smart Electric Vehicle Charging and Vehicle-to-Grid Technologies: Regulatory, Policy and Technical Aspects - Sridevi Tirunagari; Mingchen Gu; Lasantha Meegahapola (IEEE Access, 2022)
Electric vehicles (EVs) are penetrating rapidly into the transport sector while making profound impact on the electricity and energy sectors. Although EVs have many benefits, it poses several challenges to power grid operators. Uncoordinated EV charging is one of the critical issues that need to be addressed to mitigate the potential adverse effects on power grids. Smart charging and vehicle-to-grid (V2G) technologies enable smart power transfer between the EV and the grid considering network conditions and requirements. Therefore, smart charging and V2G can alleviate the adverse effects but requires policies and regulatory frameworks to increase the uptake of these technologies. This paper presents a critical review on the effects of unmanaged charging of EVs, and the benefits of smart charging and V2G considering the published research studies and real-world field trials. Simulation case studies also demonstrate the adverse effects of uncoordinated charging and the benefits of smart charging. According to this study, unmanaged charging increases the peak load, which in turn causes high power losses, voltage violations, voltage unbalance, reduction of transformer lifespan and harmonic distortion. This study has established that smart charging alleviates these network issues and brings a wide range of economic, social, and environmental benefits. In particular, role of smart charging as a mandatory requirement for attaining the net-zero decarbonization target of the transport sector is highlighted. Finally, the paper sheds light on the policy, standards and regulatory frameworks that need to be implemented to promote smart charging and V2G technologies among EV owners and charging infrastructure developers.